Effectiveness of Administration and Personnel Development of the Election Commission - Phetprai, Phuwanai; Talerngpol, Prawpicha (Journal of Management Science Nakhon Pathom Rajabhat University, 2025)
This research aims to (1) study the current situation in personnel management and development of the Election Commission Office, (2) study the problems and environment affecting the effectiveness of personnel management and development of the Election Commission Office, and (3) propose appropriate guidelines for the effectiveness of personnel management and development of the Election Commission Office. This research is a qualitative research using in-depth interviews with only 20 employees working at the central office who hold academic positions, including operational, expert, and highly expert positions. The research systematically describes and concludes with reasons referring to the theory of data organization. The research results show that (1) organizational management and the use of modern management tools for organizational development have not been given the proper importance. Therefore, personnel management and development of the Election Commission Office cannot support the missions, duties, and changing contexts. (2) the problem of insufficient personnel in all units due to the long-term lack of personnel recruitment without examinations for promotion, resulting in personnel lacking opportunities for career growth, especially the lack of training to develop personnel to become experts. This reflects the problems and environment of personnel management and development of the Election Commission Office, and (3) the following appropriate guidelines: (3.1) plan manpower and recruit personnel according to the specified characteristics at all levels; (3.2) prepare personnel with high skills or competencies to have the knowledge, skills, and competencies necessary to perform professionally. and (3.3) Strengthening good governance in supervising personnel transparently, as well as strengthening morality and ethics according to the regulations set by the office. Article history: Received 10 March 2025 Revised 7 April 2025 Accepted 9 April 2025 SIMILARITY INDEX = 0.73 %